2017
DOI: 10.3945/ajcn.116.140822
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for death in children during inpatient treatment of severe acute malnutrition: a prospective cohort study ,

Abstract: Refeeding syndrome may occur in children who are treated for malnutrition, even with moderately low plasma phosphate, and, in particular, in children with edematous malnutrition. The replacement of F-75 with unfortified rice porridge is associated with increased risk of death, which is possibly mediated by lowering plasma phosphate. The identified clinical risk factors may potentially improve the triage of children with malnutrition. This trial was registered at www.isrctn.com as ISRCTN55092738.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 28 publications
5
55
0
1
Order By: Relevance
“…Age, diarrhoea, hypoglycaemia, hypothermia, electrolyte imbalance, pneumonia and oral thrush were not associated with mortality in this cohort of children with SAM.This mortality is similar to the 24% recorded by Bachou et al over ten years earlier among patients receiving the standard of care at Mulago hospital[5]. However, the mortality recorded in this study is much higher than that reported by more recent studies conducted in elected populations: 14% in 2017 and 9.8% in 2018 by Rytter et al and Nabukeera et al respectively[6,7]. Our observational study included all severely malnourished children receiving routine care.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Age, diarrhoea, hypoglycaemia, hypothermia, electrolyte imbalance, pneumonia and oral thrush were not associated with mortality in this cohort of children with SAM.This mortality is similar to the 24% recorded by Bachou et al over ten years earlier among patients receiving the standard of care at Mulago hospital[5]. However, the mortality recorded in this study is much higher than that reported by more recent studies conducted in elected populations: 14% in 2017 and 9.8% in 2018 by Rytter et al and Nabukeera et al respectively[6,7]. Our observational study included all severely malnourished children receiving routine care.…”
supporting
confidence: 82%
“…The datasets used and/or analysed during the current study are available from the corresponding author on reasonable request. *N=Number of participants in each category whose outcome was known, 7 One of the HIV positive patients was lost to follow One of the HEU children was lost to follow up The Kaplan Meier survival curve for children with and without HIV…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Hypophosphatemia was more common in those failing the weight‐independent appetite test, but it has been argued that phosphate levels are a more relevant predictor for outcome when measured after initiation of treatment . Although the appetite test was correlated with reduced calcium levels, this could be confounded by the fact that we did not test the appetite in children with convulsions or lethargy.…”
Section: Discussionmentioning
confidence: 93%
“…As an alternative to the appetite test, the Integrated Management of Childhood Illnesses (IMCI) guidelines recommend using a list of medical complications as part of an algorithm to identify children with SAM in need of hospitalisation. To our knowledge, this IMCI algorithm has never been evaluated, although studies have assessed the prognostic value of some of the clinical signs and symptoms included in it . This set of medical complications tended to indicate a lower weight gain during follow‐up and to be associated with abnormal biochemistry results at admission.…”
Section: Discussionmentioning
confidence: 99%
“…This refeeding oedema seems to be a part of the so called refeeding syndrome with a significant mortality in highly developed medical systems but most of all in starved children in the developing world [2]. The metabolic disturbances of the refeeding syndrome are well understood and investigated.…”
Section: Editorialmentioning
confidence: 99%